Baby walkers: paediatricians' knowledge, attitudes, and health promotion. Issue 12 (11th December 2003) - Rhodes, K; Kendrick, D; Collier, J
Abstract : Paediatricians were surveyed about baby walker knowledge, attitudes, and practice. Advising about walkers was associated with working in community paediatrics, treating walker related injuries, knowledge about walkers, and positive attitudes towards walker health promotion. Greater knowledge about walkers was associated with more negative attitudes to walkers. Educating paediatricians and parents about the risks of, and alternatives to using walkers is important.